EFL Students’ Critical Thinking Skills: The Perceptions of SMA IT Wahdah Islamiyah Makassar Teachers and Students - Dian Widya Alfira; Nurdin Noni; Chairil Anwar Korompot (Journal of Excellence in English Language Education, 2022)
This study aimed to find out the perceptions of SMA IT Wahdah Islamiyah Makassar’s Teachers and Students about Critical Thinking in the learning process. The researcher used a qualitative method. The population of this research are 120 students from four classes, which are XI IPA 3, XI IPA 2, XII IPA 3 and XI IPS 2 in academic year 2020-2021, also 2 English teachers at SMA IT Wahdah Islamiyah. The sample for this research is 39 students that were selected purposively by filling out questionnaires and providing opinions and examples of critical thinking that they know, so that the results of the questionnaire can be used to see their basic knowledge about critical thinking, it is intended that the sample who conducts an interview has an idea or basic knowledge about critical thinking. This study use interview to support the research and technique of data analysis by Miles and Huberman. The result of data analysis showed that English teachers’ perceptions about critical thinking is that critical thinking are the ability to make a summary, give opinion, evaluate the information and also the ability to think rationally about what to do/believe the information/ideas. While students’ perceptions about critical thinking are that critical thinking are thinking logically, confirming, and validating the correctness of an information, and the ability to solve a problem. Teachers’ perceptions of students’ ability to think critically can be seen from the activities that occur in the classroom and factors that become problems for students in thinking critically in the classroom. Students’ perceptions of their ability to think critically can be seen from their role in applying critical thinking in the classroom. Teachers' perceptions of their role in integrating critical thinking in the lesson is encouraging students to make questions or give conclusions from the material that provided by the teacher. Students’ perceptions of their role in integrating critical thinking in the lesson can be seen from two categories, such as the problem that the students faced when they are trying to think critically in the classroom and the classroom situation. The statements above are supported by the results of in-depth interviews through focus group discussion.